Bioaktivitas Forbazol-E terhadap Kerusakan Ultrastruktur Dinding Sel Staphylococcus aureus - Ristiati, Ni Putu; Suata, Ketut; Suprapta, Dewa Ngurah (Jurnal Veteriner, 2009)
The bioactivity role of phorbazol-E in inhibiting bacterial protein synthesis is unknown. On the contrary, phorbazol-A, B, C, and D have been proved to inhibit the bacterial protein synthesis. The effect of forbazol-E on Staphylococcus aureus ATCC25922 cell wall ultrasctucture destruction was observed. The study used randomized-post test-only control group design which consist of three treatment (control, treatment I and II) with 9 repeatation. Treatment I: 1 ml overnight culture of S. aureus was cultured into a mixed of 20 ml Mueller Hinton (MH) broth and 37.5 mg/L phorbazol- E; whereas in treatment II phorbazol-E used was 75.0mg/L. The growth curve of S. aureus was monitored using spectrophotometer; whilst the destruction of cell wall ultrastructure was observed using Transmission Electron Microscope (TEM) at Eijkman Insitute, Jakarta. Phorbazol-E at 75.0mg/L significantly caused the destruction of the bacteria cell wall ultrastructure and inhibited the bacteria growth in comparison to phorbazol-E at 37.5 mg/L (p<0.05).
Keywords: forbazol-E. S. aureus.kB